Cardiac Resynchronisation Therapy: The Role of Echocardiography in Patient Selection and Follow-up - Middlemost, Shirley (SA Heart Journal, 2017)
Resynchronisation of segmental left ventricular mechanics as well as re-coordination of both atrioventricular and interventricular mechanics are potential mechanisms for the clinical improvement observed in patients undergoing cardiac resynchronisation therapy (CRT) for heart failure. Resynchronisation therapy is approved in patients with refractory heart failure symptoms despite optimal medical therapy. The presence of a prolonged QRS duration has been the main criterion used to identify ventricular dyssynchrony. However, based on the current selection criteria, about 20% to 30% of patients do not improve after biventricular pacing. Using echocardiography, dyssynchrony may be absent in some heart failure patients with a wide QRS, or present in those with a normal QRS interval. Echocardiography, and especially the more sophisticated techniques based on Tissue Doppler Imaging, may improve patient selection by identifying inter- and intra-ventricular dyssynchrony. Echocardiography can also be used to optimise lead placement. Following pacemaker implantation, various echocardiographic techniques can be used to ensure optimal cardiac resynchronisation and to monitor improvements in left ventricular function and hemodynamics. In this review, the different echocardiographic approaches to predict patient response to CRT are discussed. In addition, the use of echocardiography to guide lead positioning and to optimise pacemaker settings following pacemaker implantation is discussed.